2018
DOI: 10.1007/s00253-018-8770-6
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of acyl-ACP thioesterase activity directed for tailored fatty acid synthesis

Abstract: Medium-chain fatty acids have attracted significant attention as sources of biofuels in recent years. Acyl-ACP thioesterase, which is considered as the key enzyme to determine the carbon chain length, catalyzes the termination of de novo fatty acid synthesis. Although recombinant medium-chain acyl-ACP thioesterase (TE) affects the fatty acid profile in heterologous cells, tailoring of the fatty acid composition merely by engineering a specific TE is still intractable. In this study, the activity of a C8-C10-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…When plant TEs are overexpressed in E. coli , their substrate specificities determine the product spectrum of fatty acid synthesis . As shown by mutagenesis studies, altering TE activity relative to KAS activity can influence the product spectrum of fatty acid synthesis …”
Section: Regulation Of Fatty Acid Chain Length In Type II Fassmentioning
confidence: 99%
See 2 more Smart Citations
“…When plant TEs are overexpressed in E. coli , their substrate specificities determine the product spectrum of fatty acid synthesis . As shown by mutagenesis studies, altering TE activity relative to KAS activity can influence the product spectrum of fatty acid synthesis …”
Section: Regulation Of Fatty Acid Chain Length In Type II Fassmentioning
confidence: 99%
“…[2a] As shown by mutagenesiss tudies, altering TE activity relativet oK AS activity can influencet he product spectrum of fatty acid synthesis. [134] Directed Engineering for Modulation of Fatty Acid Chain Length Fatty acids are considered strategically important platform chemicals accessible throughs ustainable microbial approaches. [135] The recently acquired structurali nformation on FASs provides an excellent understandingo ft he molecular basis of fatty acids ynthesis.…”
Section: Regulation Of Fatty Acid Chain Length In Type II Fassmentioning
confidence: 99%
See 1 more Smart Citation
“…This thioesterase acts as a dimer, its monomers establishing two tandem hot dog folds that are joined by a flexible linker, one close to the C-terminal domain and other close to the N-terminal one. The N-terminal hot dog domain defines the substrate binding pocket, which can be engineered to change the substrate specificity of the enzyme ( Feng et al, 2018 ). This Uc FatB1 is more closely related to other plant thioesterases than to any bacterial isoforms and thus, the structure of this enzyme is likely to be a better reference to model FatA and FatB2 enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HSL1dependent histone methylation plays critical roles in regulation of seed dormancy during seed germination and early seedling growth, which will affect the oil content accumulated in seed [53]. Similarly, AtLPEAT2 [54], AtLACS2 [55] and ChACP4 [56] were found to be associated with PI (34:3), linolenic acid (P = 2.63e-07), and pyruvate (LOD = 14.68) in oil synthesis process, respectively. Ma et al [39] also found that the cotton genes GhHSL1, GhACP2 and GhLPEAT2 were differentially expressed between the upland cotton (G. hirsutum L.) high oil content genotype (3008) and low oil content genotype (3012) in 10, 20 and 30 DPA ovules.…”
Section: Discussionmentioning
confidence: 96%